Accounting education in a developing nation focus: Malaysia / Dorin Thomas Stuel - Thomas Stuel, Dorin (1992)
In Malaysia, accounting education can be obtained either through the universities or institutions of higher learning or through apprenticeship training with public accounting firms. The design of university programme and curriculum is usually based on either traditional subject matter or felt needs. MIA and MACPA are also playing an important role as a professional bodies regulating, controlling and 'watching over' the profession.